Nondestructive Measurement of Momentum Transfer Collision Frequency for Low Temperature Combustion Plasma - Douglas Letsholathebe; Kgakgamatso M. Mphale; Samuel Chimidza (International Journal of Antennas and Propagation)
Accurately measured momentum transfer collision frequency and electron density for fire plasma enable correct simulation of electromagnetic wave propagation in the medium. The simulation is essential for designing high-performance systems suitable for the environment. Despite this, momentum transfer collision frequency for fire plumes has always been an estimated quantity and/or crudely determined. There are anecdotal reports of severe line-of-sight (LOS) radio frequency signal degradation on firegrounds. The problem has implications on safety of fire-fighters during wildfire suppression hence the need of high performance communication systems. In the experiment, a nonintrusive and direct method for measuring momentum transfer collision frequency in a fire plume was carried out. Using an automatic network analyser, x-band microwaves were caused to propagate combustion zones of eucalyptus and grass litter fires to measure the flames, scattering parameters. The parameters were then used to determine average collision frequencies for the plumes. The average collision frequencies for the eucalyptus and grass fire plumes were measured to be 5.84×1010 and 5.92×1010 rad/s, respectively.